EXPERIMENTAL STUDY ON LOAD - DAMPING EFFECTS OF THE STRUCTURES IN UNDERWATER SHOCK WAVES IN TRUONG SA ARCHIPELAGO - Loi, Vu Dinh; Tho, To Duc; Lai, Nguyen Tuong; Tuan, Le Anh; Nghi, Nguyen Cong (Vietnam Journal of Marine Science and Technology, 2015)
Research on the problem of load damping of the structures under the effect of shock waves in environment generally and in water particularly is important and necessary for military structures and buildings of inhabitants. If properly designed and having solution to reduce the effects of the blast wave, general structures will be increased markedly and reduce ability of being destroyed. One of the solutions to reduce the effects of the blast wave is to glue layers of material having capable of absorbing blast waves onto the structures. The theoretical and empirical studies are currently less pronounced due to many different reasons. This paper presents modeling and experimental results from the underwater explosion topic KC09.06/11-15 in Truong Sa archipelago to determine the damping effect of the structure modeling is designed with layers of featured material on its surface.